(untitled) (Physical Education, Health and Social Sciences, 2026)
The study aimed to investigate the management of the social-emotional adjustment issues of students with hearing impairments. The study used sequential explanatory mixed-method research design. A sample of 104 teachers of students with hearing impairment were selected for quantitative phase and 8 teachers were selected for in-depth interviews by using the purposive sampling technique. In quantitative phase, the data was collected using a standardized scale, the Social-Emotional Issues adapted scale (47 items) and for qualitative phase, interview protocol was used to collect data. The collected quantitative data were analyzed using IBM SPSS Statistics. For qualitative data, thematic analysis was used. The results indicated significant gender-based differences in the temper regulation factor, male teachers demonstrating higher scores than their female teachers. However, no substantial differences were observed in social assertiveness, mood stability, and the level of anxiety. Additionally, the study examined the impact of the education sector on social and emotional issues, revealing a marginally significant difference in social assertiveness, where teachers from private institutions reported higher scores. Furthermore, a one-way ANOVA explored the influence of job experience on social and emotional aspects, showing no statistically significant mean differences among different experience groups. In conclusion, this research sheds light on gender-related variations in social and emotional issues among students with hearing impairments. The findings provide valuable insights for educators and institutions to tailor support strategies. Further research is recommended to explore additional factors influencing social and emotional adjustment issues in this teacher’s demographic.